Strategies to promote the meaningful involvement of sex workers in HIV prevention and care. Issue 5 (September 2019) - Cowan, Frances M.; Reza-Paul, Sushena; Ramaiah, Manjula; Kerrigan, Deanna L.
Abstract : Purpose of review: We review the recent evidence regarding strategies for engaging sex workers in HIV prevention and care programs. We searched Pub Med on 19 March 2019 using terms 'Sex Work' And 'HIV infections'. Our search was limited to articles published since 2017. Recent findings: Community empowerment approaches where sex workers work collaboratively to address their specific priorities and concerns, including those beyond HIV, are those most likely to meaningfully engage sex workers. Community-driven programs that combine structural, behavioral and biomedical approaches can facilitate improved HIV outcomes by tackling barriers to uptake and retention of services along all steps in the prevention and care cascades. Microplanning, network-based recruitment and mobile-phone interventions can also help reach and support sex workers to mobilize and to engage with a range of services. Sex worker-led groups and initiatives including economic strengthening and community drug refill groups can both build social cohesion and address structural barriers to HIV outcomes including financial insecurity. Interventions which focus narrowly on increasing uptake of specific steps in prevention and care cascades outside the context of broader community empowerment responses are likely to be less effective. Summary: Comprehensive, community-driven approaches where sex workers mobilize to address their structural, behavioral and biomedical priorities work across HIV prevention and treatment cascades to increase uptake of and engagement with prevention and care technologies and promote broader health and human rights. These interventions need to be adequately supported and taken to scale.